Sutika Swasthavritta – A Rejuvenation Therapy - Sharma, Nitika; Mishra, Pramod Kr; Sharma , DivyaDeepak (International Research Journal of Ayurveda & Yoga, 2024)
The word “Sutika” signifies a woman has delivered a child along with the placenta. The scientific interpretation of Sutika is puerperal woman, all the classics have advised proper adherence to “SutikaSwasthavritta” as advised in Ayurveda classics results in faster restoration of health of a mother and to attain proper health after puerperium and rejuvenates. AcharyaKashyapa has defined the birth of child as “Rebirth” of mother. The word rebirth signifies the pain and hardships she has to undergo while delivering a baby. Hence, she needs utmost level of care after delivery. The “Sutika” recovers from her labour which often leaves her tired and exhausted. There is, never the less feeling of great relief and happiness. The “Sutika” undergoes what is probably the most important psycho physiological experience of her life; she realizes that she is responsible for another human. “Sutika” is prone to many diseases, and hence it is must to follow “SutikaSwasthavritta” which not only improves her physiological condition but also protects her from upcoming diseases. In general, all Acharyas’have explained massage, oral administration of sneha, decoctions, medicated rice gruel, medicated soups to overcome this problem and scientifically explained “SutikaSwasthavritta”. So an attempt is made.